A brief comparison of polygenic risk scores and Mendelian randomisation - Victoria Garfield; Emma L. Anderson (BMC, 2024)
Abstract Mendelian randomisation and polygenic risk score analysis have become increasingly popular in the last decade due to the advent of large-scale genome-wide association studies. Each approach has valuable applications, some of which are overlapping, yet there are important differences which we describe here.